2002
DOI: 10.4141/p01-008
|View full text |Cite
|
Sign up to set email alerts
|

Response of bean to applications of hydrophobic mineral particles

Abstract: Tworkoski, T. J., Glenn, D. M. and Puterka, G. J. 2002. Response of bean to applications of hydrophobic mineral particles. Can. J. Plant Sci. 82: 217-219. Foliar applications of hydrophobic mineral particles can protect plants from some insects, but plant response to particle applications is not known. Bean (Phaseolus vulgaris L.) plants were grown for 8 wk in a greenhouse and the shoots were sprayed weekly with small-diameter hydrophobic mineral particles. Photosynthesis was similar in particle-treated and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…These results are in agreement with those obtained for bean (Tworkoski et al, 2002), as well as for other species, such as tomato and tea (Anandacoomaraswamy et al, 2000;Cantore et al, 2009) at a leaf and/or whole plant scale. However, they are contrary to the findings of Glenn et al (1999), who found that kaolin, marketed as Surround ® WP, due to its particular physical characteristics, does not impede g s and gas exchange in apple.…”
Section: Tablesupporting
confidence: 93%
“…These results are in agreement with those obtained for bean (Tworkoski et al, 2002), as well as for other species, such as tomato and tea (Anandacoomaraswamy et al, 2000;Cantore et al, 2009) at a leaf and/or whole plant scale. However, they are contrary to the findings of Glenn et al (1999), who found that kaolin, marketed as Surround ® WP, due to its particular physical characteristics, does not impede g s and gas exchange in apple.…”
Section: Tablesupporting
confidence: 93%
“…On tomato, in agreement with reduction of A and E at leaf scale, Cantore et al (2009a) found also the reduction of net assimilation and evapotranspiration at canopy scale. The reduction of g s and, therefore, of E caused by the kaolin is also reported for many species such as apple (Le Grange et al 2004), pecan (Lombardini et al 2005), tea (Anandacoomaraswamy et al 2000), pepper (Sheikh & Mall 1978), bean (Tworkoski et al 2002;Cantore et al 2009b), Polianthes tuberosa L. (Moftah & Al-Humaid 2005), orange (Pace et al 2009), tomato (Srinivasa Rao 1985, 1986Nakano & Uehara 1996;Cantore et al 2009a) and potato (Cantore unpublished data). On grapevine, however, g s was reduced in well-watered crop, while it was not affected in stressed one (Shellie & Glenn 2008).…”
Section: Discussionmentioning
confidence: 59%
“…(Russo and Diaz-Perez, 2005), walnut (Juglans regia), almond (Prunus dulcis) (Rosati et al, 2006), and beans (Tworkoski et al, 2002); whereas some others reported significant reduction in carbon assimilation with PFs at the leaf level (Le Grange et al, 2004;Wunsche et al, 2004) which they attributed primarily to the reduced light at leaf surface, but none of these studies have linked leaf level responses to plant yield. The work by Glenn et al (2001bGlenn et al ( , 2002 suggested that under excessive heat conditions (air temperatures above 30°C), the kaolin applications reduced temperature, and thereby increased carbon assimilation and stomatal conductance.…”
Section: Carbon Assimilationmentioning
confidence: 96%